Beyond mere repetition: On tradition, creativity and theological speech - Vosloo, Robert (HTS teologiese studies, 2023)
This article argues for understanding Christian theological speech, including a Reformed engagement with confessions, as ‘traditioned creativity’. The argument is introduced by highlighting a theological hermeneutic that underlies the Belhar confession’s accompanying letter. This discussion points towards an account of Christian discourse that is ‘traditioned’ by the past but also moves beyond the mere repetition of the tradition’s authoritative statements. The article, therefore, affirms the need to distinguish between a living tradition and a narrow traditionalism. In addition, the article also interrogates some forms of theological rhetoric in which ‘tradition’ functions to insert control over spaces and people, often exhibiting totalising discourses and over-triumphant claims.Contribution: The conclusion links a hermeneutic of tradition (that sees Christian speech, doctrine and action as ‘traditioned creativity’) to some metaphors that can further illuminate what it means for a tradition to be open to the future in a way that displays vulnerability and vitality.